2014
DOI: 10.1099/jmm.0.081711-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Pinus elliottii and its major compound, dehydroabietic acid, against multidrug-resistant strains

Abstract: Antibiotic-resistant bacteria have emerged from the widespread use of antibiotics worldwide and have prompted the search for new sources of antimicrobial substances. Pinus spp. contain several bioactive compounds consisting mainly of terpenes, terpenoids and some other aromatic and aliphatic constituents. These compounds exert important biological effects, and pine oils have found wide application in the industry. In the present study, we have evaluated the potential activity of the resin-oil of Pinus elliotti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…The oxidized resin acids occurred in emulsions in low concentrations, in range of some hundreds of ppms at most. In earlier literature, the main resin acids, like abietic acid and dehydroabietic acid, are shown to be antimicrobial (S€ oderberg et al 1990;Leandro et al 2014;Gogulramnath et al 2015). These main resin acids are not, however, water soluble and will not be transferred into aqueous emulsions or dispersions as the case is with the oxidized resin acids.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidized resin acids occurred in emulsions in low concentrations, in range of some hundreds of ppms at most. In earlier literature, the main resin acids, like abietic acid and dehydroabietic acid, are shown to be antimicrobial (S€ oderberg et al 1990;Leandro et al 2014;Gogulramnath et al 2015). These main resin acids are not, however, water soluble and will not be transferred into aqueous emulsions or dispersions as the case is with the oxidized resin acids.…”
Section: Discussionmentioning
confidence: 99%
“…As readily available materials, the two resin acids have been extensively studied for their biological properties, and showed activity (at concentrations above 5 μg mL −1 ) in antibacterial assays e.g. 39 40 41 . Metabolite 1 was also found to inhibit methanogenesis in different bacteria 42 , to have anti-ageing activity in C. elegans 43 , mild cytotoxicity against cancer cell lines 44 and antifungal activity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported in the literature for other pine species have shown that abietic acid and dehydroabietic acid have a strong antimicrobial activity against gram-positive bacteria, being dehydroabietic acid the most effective of all simple resin acids [4,[15][16][17][18][19][20]. The differences in antibacterial efficacy detected among the different reports found in the literature are due to the fact that the studied rosins come from different species and the growth conditions, the recovery processes, the concentrations of the different resin acids, the neutral fraction, the storage and age are factors that affect the quality of rosin.…”
Section: Resultsmentioning
confidence: 99%